Genetic Engineering and Enrichment of Human NK Cells for CAR-Enhanced Immunotherapy of Hematological Malignancies - Soldierer, Maren; Bister, Arthur; Haist, Corinna; Thivakaran, Aniththa; Cengiz, Sevgi Can; Sendker, Stephanie; Bartels, Nina; Thomitzek, Antonia; Smorra, Denise; Hejazi, Maryam; Uhrberg, Markus; Scheckenbach, Kathrin; et al. (Frontiers in Immunology, 2022)
With their great clinical success, chimeric antigen receptor (CAR) T cells have unlocked new levels of immunotherapy for hematological malignancies. Genetically modifying natural killer (NK) cells as alternative CAR immune effector cells is also highly promising for the treatment of malignancies, as NK cells can be transplanted across HLA barriers without causing graft-versus-host disease and therefore off-the-shelf usage of CAR NK cell products might allow to widely expand the clinical indications and to limit the costs per patient. However, in contrast to T cells, manufacturing of suitable CAR NK cell products is still challenging, as standard techniques for genetically engineering NK cells are still being defined. In this study, we have established optimal lentiviral transduction of primary human NK cells by systematic testing of different internal promoters for lentiviral CAR vectors and comparing lentiviral pseudotypes and viral entry enhancers. We have additionally modified CAR constructs recognizing standard target antigens for ALL and AML therapy, CD19, CD33 and CD123, to harbor a CD34-derived hinge region, that allows efficient detection of transduced NK cells in vitro and in vivo and also facilitates CD34 microbeads-assisted selection of CAR NK cell products to >95% purity for potential clinical usage. Importantly, as most leukemic blasts are a priori immunogenic for activated primary human NK cells, we developed an in vitro system that blocks the activating receptors on these cells and therefore is suitable to systematically test the specific killing of CAR NK cells against ALL and AML cell lines and primary AML blasts. Finally, we evaluated in an ALL xenotransplantation model, how much human CD19 CAR NK cells directed against the CD19+ blasts are relying on soluble or membrane-bound IL15 production for NK cell persistence and also in vivo leukemia control. Therefore, this study provides important insights into the generation of pure and highly active allogeneic CAR NK cells, thereby advancing adoptive cellular immunotherapy with CAR NK cells for human malignancies further.